RNAi in Pest Control: Critical Factors Affecting dsRNA Efficacy - Maribel Mendoza-Alatorre; Brenda Julian-Chávez; Stephanie Solano-Ornelas; Tania Samanta Siqueiros-Cendón; Jorge Ariel Torres-Castillo; Sugey Ramona Sinagawa-García; María Jazmín Abraham-Juárez; Carmen Daniela González-Barriga; Quintín Rascón-Cruz; Luis Ignacio Siañez-Estrada; Edward Alexander Espinoza-Sánchez (Insects, 2025)
In recent years, agricultural crops have increasingly been attacked by more destructive insect pests, forcing modern farming to depend mainly on chemical insecticides. Although valuable, their widespread and intensive misuse has raised serious concerns about environmental and public health impacts. RNAi has been proposed as a safer alternative due to its high specificity, adaptability, and low ecological footprint. So far, dsRNA has proven effective in controlling various pest species, either through topical application or via genetically modified plants. Despite advances, large-scale implementation of RNAi remains challenging due to technical and biological hurdles that contribute to inconsistent performance. Key aspects such as dsRNA design, delivery techniques, and cellular uptake mechanisms still require refinement. Additionally, ensuring environmental stability, addressing biosafety concerns, and developing cost-effective production methods are essential for its practical application. In this review, we explore recent advances in the design and implementation of dsRNA, as well as the strategies that could support the successful integration of RNAi technology into pest management programs.